Influences of dietary supplementation with Lepidium meyenii (Maca) on stallion sperm production and on preservation of sperm quality during storage at 5 °C. (22nd January 2018) - Del Prete, C.; Tafuri, S.; Ciani, F.; Pasolini, M. P.; Ciotola, F.; Albarella, S.; Carotenuto, D.; Peretti, V.; Cocchia, N.
Summary: Stallion semen is damaged by oxidative stress during cooling and transport. Semen processing and extenders have been tested to improve the fertilizing capacity of semen and to preserve semen during transport. Dietary supplementation with natural antioxidants has been proposed to prevent oxidative damages. In this study, for the first time, the effect of dietary supplementation with Lepidium meyenii (Maca) on the characteristics of fresh and chilled stallion semen was evaluated. Maca is a traditional Andean crop used as a nutraceutical for the fertility‐enhancing properties that are linked with antioxidant activity. The diet of five stallions was supplemented with 20 g of Maca powder daily for a total of 60 days. A control group of five stallions received the same diet without Maca. Semen was collected once before the administration of Maca (D0), twice during the administration at 30 and 60 days (D30 and D60), and finally twice at 30 and 60 days after the end of the administration (D90 and D120). Ejaculates were processed for cooled shipping at 5 °C and evaluated in the laboratory for total and progressive motility, acrosome integrity, and lipid peroxidation after collection and after 24, 48, and 72 h of storage. Dietary supplementation with Maca improved sperm concentration (from 213 ± 80.4 to 447 ± 73.1 × 10 6 spz/mL) and total sperm count (from 10, 880 ± 4377 to 24, 783 ± 4419 × 10 6 spz). The beneficial effects of Maca supplementation on motility and acrosome integrity in the raw semen were detected from the end of treatment with Maca (D60) until the end of the study (D120). Furthermore, during cooling storage, total motility, progressive motility, and acrosome integrity declined more slowly in the Maca‐treated group than in the control group. Lipid peroxidation did not change during cooling storage in either group and did not show a significant difference between the two groups. In this study, the dietary supplementation with Maca increased sperm production and stabilized semen quality during chilled storage.